Legal Protection for Micro Business Actors in the Gig Economy - Palit, Silvester Magnus Loogman; Zaki, Amin; Razak, Faisal; Huda, Nurul; Dwiatmanto, Dwiatmanto (Rechtsnormen: Journal of Law, 2024)
Background. The gig economy has seen substantial growth in recent years, characterized by short-term, flexible work arrangements. Micro business actors, including freelancers and independent contractors, are significant contributors to this economy. However, they often lack the legal protections and benefits afforded to traditional employees, exposing them to various risks such as unstable income, lack of health benefits, and insufficient legal recourse in disputes. Purpose. This study aims to evaluate the current legal protections available for micro business actors in the gig economy. The research seeks to identify gaps in the legal framework and propose solutions to enhance the protection and support for these workers. The goal is to ensure fair treatment and security for micro business actors, thereby promoting a more equitable and sustainable gig economy. Method. A mixed-methods approach was employed, combining quantitative surveys and qualitative interviews. Quantitative data were collected from 300 micro business actors across various sectors of the gig economy, assessing their awareness and experience with legal protections. Results. Findings indicate significant gaps in the legal protections for micro business actors. Only 25% of survey respondents reported feeling adequately protected under current laws. Common issues identified include lack of access to social security benefits, inadequate dispute resolution mechanisms, and insufficient regulatory oversight. Interviewees highlighted the need for updated legal frameworks that recognize the unique nature of gig economy work. Conclusion. The research underscores the urgent need for enhanced legal protections for micro business actors in the gig economy. Implementing comprehensive legal reforms can address existing gaps, providing these workers with the security and support they need.